Agro-ecological cultivation, secondary metabolite characteristics and microbiological tests of lemon balm (Melissa officinalis) – the variety Citronella - I. Salamon; M. V. Kryvtsova; K. I. Trush; A. I. Fandalyuk; M. J. Spivak (Regulatory Mechanisms in Biosystems, 2019)
Lemon balm (Melissa officinalis L.) is a native of the eastern Mediterranean region southward to Israel and Syria and eastward through the Crimea, the Caucasus, and Northern Iran to the Tien Shan and the Pamirs. It appears to have been naturalized in the Central Europe including the Carpathian Ukraine and Eastern Slovakia. The objective of this study was characterization of the chemical composition and antimicrobial activity of essential oils from Melissa officinalis L. variety Citronella in the conditions of cultivation in a lowland region of the Ukrainian Carpathians. Plant material, balm dry leaves and leafy tops of the shoots, were grown in a small-scale cultivation ground at the Zakarpatian Institute of Agroindustrial Production in Velikaja Bakta, Carpathian-Ukraine. The Citronella variety is used for herb production. Essential oil from balm parts (herb and leaves) was isolated by distillation with boiled water. Hydro-distillation lasted for 4 hours, sample weights were 10 g of dry drug matter. A modified Coocking & Middleton distillation apparatus was used. Identification and evaluation of balm essential oil were carried out using the selected analytical method of HPLC-DAD analysis. The final balm extract was analyzed directly on a Dionex UltiMate 3000 system. The analysis of balm essential oil was carried out using a gas chromatograph Varian 3090, connected to a MS Saturn 2100T integrator. The sensitivity of microorganisms to plant extracts was determined by the disk diffusion test (with disk diameter of 6 mm). The quantitative and qualitative characteristics of balm essential oil (0.05–0.12% v/w) and its composition show very high content of α-citrale (geranial) (44%), β-citrale (neral) (29%) and citronellal (9%). Rosmarinic acid can be extracted from leaves and its content equals up to 1.7 ± 0.1%. Composition of the natural substances depends on the balm taxon, origin, soil and climatic growing conditions, and methods of harvest and isolation and effective weed control which are used. Antibacterial effect of the oil showed low activity against all bacterial strains. Our results confirmed higher activity of EOs against Gram-positive bacteria than Gram-negative. The balm essential oil displayed antimitotic effect especially towards Candida glabrata clinical strain. Thus, studies have shown that Melissa officinalis variety of Citronella in the conditions of cultivation in the lowland region of Carpathian-Ukraine according to biochemical characteristics and microbiological properties corresponds to world analogues.